2017
DOI: 10.1016/j.tsf.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent thermal properties of amorphous insulating thin films measured by photoreflectance microscopy

Abstract: In this work, we report on the measurement of the thermal conductivity of thin insulating films of SiO 2 obtained by thermal oxidation, and Al 2 O 3 grown by atomic layer deposition (ALD), both on Si wafers. We used photoreflectance microscopy to determine the thermal properties of the films as a function of thickness in the 2 nm to 1000 nm range. The effective thermal conductivity of the Al 2 O 3 layer is shown to decrease with thickness down to 70% for the thinnest layers. The data were analyzed upon conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…There are four unknowns: the interface resistance R int , the contact radius a, the thermal conductivity of the layer k and the interface thermal resistance between the layer and the substrate r int . We obtained a realistic contact radius of a = 65.5 nm as well as for the ther-mal conductivity of the silicon oxide layers k = 1.0 Wm −1 K −1 being in a good agreement with optical technique measurements of similar sample [143]. The value of interface thermal resistance obtained (r int = 4.91 × 10 −8 m 2 KW −1 ) is around one order of magnitude higher than that found by Chien et al [144] but similar to that found by Zhu et al [145].…”
Section: Silicon Oxide Stepssupporting
confidence: 83%
See 1 more Smart Citation
“…There are four unknowns: the interface resistance R int , the contact radius a, the thermal conductivity of the layer k and the interface thermal resistance between the layer and the substrate r int . We obtained a realistic contact radius of a = 65.5 nm as well as for the ther-mal conductivity of the silicon oxide layers k = 1.0 Wm −1 K −1 being in a good agreement with optical technique measurements of similar sample [143]. The value of interface thermal resistance obtained (r int = 4.91 × 10 −8 m 2 KW −1 ) is around one order of magnitude higher than that found by Chien et al [144] but similar to that found by Zhu et al [145].…”
Section: Silicon Oxide Stepssupporting
confidence: 83%
“…Then, we can use the 300 nm oxide sample as a calibration sample for the effective contact radius. By assuming literature values for the thermal conductivity (k SiO 2 ≈ 1W/mK [143,167]) and the interface thermal resistance between silicon oxide and silicon (r int Si−SiO 2 ≈ 1 × 10 −9 m 2 K/W [143,168]), we are left only with the effective contact radius. With these parameters, we obtained a = 56.1nm .…”
Section: Quantitative Measurements Of Thermal Conductivity and Interfmentioning
confidence: 99%
“…Because the amorphous layer has lower thermal conductivity than the bulk materials, the increase of the amorphous layer thickness also has impact on the thermal boundary conductance. As reported, the thermal conductivity of the amorphous layer decreases by 70% when the thickness increases from 2 nm to 1000 nm [28]. Obviously, the decrease in the thermal conductivity of the amorphous layer formed at the diamond/InGaP interface due to the amorphous layer thickness increasing in several nanometers can be ignored.…”
Section: Resultsmentioning
confidence: 82%
“…Thermo-reflectance microscopy was used elsewhere [30] to measure the thermal conductivity kSiO2 of the sample, providing an intrinsic conductivity value for the SiO2 as well as the thermal resistance at the boundary rtbr between the SiO2 film and the Si substrate. Values determined are kSiO2 = 1.1 W.m -1 .K -1 and rtbr = 4.4 10 -8 m 2 .K.W -1 .…”
Section: Sample a Sample Description And Characteristicsmentioning
confidence: 99%
“…(1) at the sample surface and at the thin film/substrate boundary (z = t) for two heat source radii b (100 and 300 nm) and two film thicknesses t (237 and 65 nm). Thermoreflectance data was used for the the silicon dioxide film thermal conductivity and the thermal resistance at the boundary with silicon [30]. Fig.…”
Section: B Sample Modellingmentioning
confidence: 99%